2022
DOI: 10.1177/10820132221097879
|View full text |Cite
|
Sign up to set email alerts
|

Early postmortem degradation of actin muscle protein in Algerian Sahraoui dromedaries

Abstract: The present study aimed to evaluate actin degradation during the early postmortem time in Longissimus Lumborum muscle according to Sahraoui dromedary's age. A sample of eight males, young (2 years old) and adult (8 years old) dromedaries, was used to investigate meat quality traits and actin proteolysis during the conversion of muscle to meat. Results demonstrated higher pH values in young compared to adult with a polyphasic pH drop profile. While, age did not affect drip loss (DL) and the values at 72 h postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…However, it is reported that this degradation can give rise to fragments of 32 and 30 kDa after ageing of pork [36] and beef [9,37], respectively. Similarly, the generation of the 32 kDa Actin fragment in dromedary meat up to 24 h post-mortem was recently observed [38], suggesting that this Actin degradation pattern would occur for all animal species. The amount of this 32 kDa fragment still observed in horse meat at 21 d post-mortem would correspond to a minor amount that had not been further degraded to smaller fragments [39].…”
Section: Fig 2 Functional Protein-protein Association Network Of Prot...mentioning
confidence: 61%
“…However, it is reported that this degradation can give rise to fragments of 32 and 30 kDa after ageing of pork [36] and beef [9,37], respectively. Similarly, the generation of the 32 kDa Actin fragment in dromedary meat up to 24 h post-mortem was recently observed [38], suggesting that this Actin degradation pattern would occur for all animal species. The amount of this 32 kDa fragment still observed in horse meat at 21 d post-mortem would correspond to a minor amount that had not been further degraded to smaller fragments [39].…”
Section: Fig 2 Functional Protein-protein Association Network Of Prot...mentioning
confidence: 61%